A Case of Peripheral Ulcerative Keratitis Associated with Autoimmune Hepatitis - Hamoon Eshraghi; Aria Mahtabfar; Mohammad H. Dastjerdi (Case Reports in Medicine)
Purpose. To describe a case of peripheral ulcerative keratitis in the setting of autoimmune hepatitis and possible overlap syndrome with primary sclerosing cholangitis. Case Report. A 48-year-old African American female with autoimmune hepatitis with possible overlap syndrome with primary sclerosing cholangitis presented with tearing, irritation, and injection of the left eye that was determined to be peripheral ulcerative keratitis. The patient was treated with topical and systemic steroids, immunosuppressant drugs (azathioprine and mycophenolate mofetil), a biologic (rituximab), and surgery (conjunctival resection), and the peripheral ulcerative keratitis epithelialized but ultimately led to corneal perforation. Conclusion. In this unique case, a patient with peripheral ulcerative keratitis who underwent treatment ultimately had a corneal perforation. This case may suggest a possible relationship between autoimmune hepatitis and peripheral ulcerative keratitis.